Tata Cara Pengendalian Pada Unit Pengadaan Barang Dan Jasa Di PT. Kereta Api Indonesia DAOP VIII Surabaya - Ivar Isma Gymnastiar; Siti Ning Farida (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
This research aims to determine the control procedures or operating procedures in the goods and services procurement unit at PT. Indonesian Railways DAOP VIII Surabaya. The research method used in this research is qualitative research, namely literature study and field research. Where the data collection system in this research comes from journals which are analyzed in the form of explanations in the form of information originating from within and from outside agencies related to the goods and services procurement system. The results of the research show that in the goods and services procurement unit there are control procedures in the form of understanding activities regarding Tenders, Work Plans and Conditions (RKS), Procurement Implementation Orders (SP3), as well as Work Terms of Reference (KAK), archive management, Aanwizjing , checking completeness of documents, negotiations, and assistance to users who need or are carrying out procurement activities.